Metformin, the Rise of a New Medical Therapy for Endometriosis? A Systematic Review of the Literature - Stochino-Loi, Emanuela; Major, Attila L.; Gillon, Tessa E. R.; Ayoubi, Jean-Marc; Feki, Anis; Bouquet de Joliniere, Jean (Frontiers in Medicine, 2021)
Medical treatments for endometriosis aim to control pain symptoms and stop progression of endometriotic lesions. However, their adverse effects and their contraceptive effect in women who desire pregnancy, limit their long terms use. Although there is only one study investigating the effects of metformin on women with endometriosis, metformin seems to have a unique therapeutic potential. It may be a helpful anti-inflammatory and antiproliferative agent in the treatment of endometriosis. As such metformin may be more beneficial thanks to the lack of serious side effects.